ASSESSMENT OF RELIABILITY OF THE ONBOARD EQUIPMENT OF SMALL SPACECRAFTS DURING THEIR FLIGHT - L. I. Kulbak; V. B. Aliushkevich; S. A. Zolotoy (Informatika)
The technique of an assessment of current state of reliability of the onboard equipment of small spacecrafts during their flight is given. А mathematical representation of the reliability indicator of onboard equipment and the model of structure of a small spacecraft, as well as formulas for calculating the fail-safe functioning indicators of realibility diagram blocks of onboard equipment are adduced.